Adsorption Studies of Cyanide (CN)- on Rice Husk Ash (RHA) - Naeem, S; Zafar, U; Amann, T (Bangladesh Journal of Scientific and Industrial Research, 2011)
In this investigation, adsorption of cyanide has been studied by means of batch-technique. Percentage adsorption was determined for Rice Husk Ash (RHA)-Cyanide solution system as a function of i) contact time, ii) pH, iii) adsorbate concentration and iv) temperature. Adsorption data has been interpreted in terms of Freundlich and Langmuir equations. Thermodynamics parameters for the adsorption system have been determined at three different temperatures. The value of ΔH°=38.326KJ/mole and ΔG°=-6.117KJ/mole at 283°K suggest that the adsorption of cyanide on RHA is an endothermic and a spontaneous process. Key words: Cyanide; Rice husk ash (RHA); Adsorption Isotherms DOI: http://dx.doi.org/10.3329/bjsir.v46i1.3524 Bangladesh J. Sci. Ind. Res. 46(1), 101-104, 2011